2014
DOI: 10.1155/2014/795104
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Shiga Toxin-ProducingEscherichia coliIsolated from Ground Beef Collected in Different Socioeconomic Strata Markets in Buenos Aires, Argentina

Abstract: Consumption of raw/undercooked ground beef is the most common route of transmission of Shiga toxin-producing E. coli (STEC). The aim of the study was to determine the STEC contamination level of the ground beef samples collected in 36 markets of different socioeconomic strata in Buenos Aires, Argentina, and the characterization of the isolated strains. Ninety-one out of 252 (36.1%) samples were stx+. Fifty-seven STEC strains were recovered. Eleven STEC strains belonged to O157 serogroup, and 46 to non-O157 ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
(59 reference statements)
2
14
3
1
Order By: Relevance
“…The proportion of ground beef samples testing positive for E . coli O157:H7 (11.6% and 3.5% in 2010–2011 and 2013, respectively) was similar to the 15.0% reported by Llorente et al [ 45 ] for ground beef from butcher shops in Argentina. On the other hand, the range of E .…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of ground beef samples testing positive for E . coli O157:H7 (11.6% and 3.5% in 2010–2011 and 2013, respectively) was similar to the 15.0% reported by Llorente et al [ 45 ] for ground beef from butcher shops in Argentina. On the other hand, the range of E .…”
Section: Discussionsupporting
confidence: 87%
“…Although this study tested for all the main DEC pathotypes, only STEC strains were found. This is not so surprising as the main ingredient of kibbe is ground beef which is considered one of the most important vehicles for the transmission of STEC (Llorente, Barnech, Irino, Rumi, & Bentancor, 2014;Mora et al, 2007). However, the presence of STEC strains in kibbe samples is of great concern because this type of food is usually eaten raw, and thus could lead to human contamination.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12] All of the ready to eat food samples of our investigation were meat-based ready to eat foods. Some of them like sausage, salami and soup were Article produced in high temperature and therefore were free from any pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%